2021
DOI: 10.4102/sajems.v24i1.3796
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the potential economic welfare to be gained by the South African Customs Union from trade facilitation

Abstract: Background: Trade facilitation is important for the South African Customs Union (SACU) countries because the expansion of international trade is a priority to enhance their economic growth. Unfortunately, the high trade compliance costs facing importers and exporters operating in SACU are in conflict with this objective.Aim: This article aims to quantify the annual economic welfare gains that the member countries of SACU could realise from reforms that would reduce the documentary and border compliance time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…According to Otsuki, Honda and Wilson (2013), trade facilitation is related to changes in the trade environment in terms of reforms, modernisation and simplification of the requirements with the aim of reducing time and saving on costs of trade. Safaeimanesh and Jenkins (2021) on the other hand describe the process of trade facilitation as the implementation of key policies that ensure that there is seamless trade with efficient communication and transport infrastructure among the Regional Trade Organization (RTO) member countries. Trade facilitation measures are recognised to be essential in helping to strengthen trade ties between countries, thus speeding-up the process of economic growth and development (OECD, 2019).…”
Section: Striking a Balance Between Customs Administration And Trade ...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Otsuki, Honda and Wilson (2013), trade facilitation is related to changes in the trade environment in terms of reforms, modernisation and simplification of the requirements with the aim of reducing time and saving on costs of trade. Safaeimanesh and Jenkins (2021) on the other hand describe the process of trade facilitation as the implementation of key policies that ensure that there is seamless trade with efficient communication and transport infrastructure among the Regional Trade Organization (RTO) member countries. Trade facilitation measures are recognised to be essential in helping to strengthen trade ties between countries, thus speeding-up the process of economic growth and development (OECD, 2019).…”
Section: Striking a Balance Between Customs Administration And Trade ...mentioning
confidence: 99%
“…Moreover, the stipulation of their roles and their integration has not been put across to clearly describe how they implement key trade facilitation policies in the region. Evidence from other regions such as Europe (Safaeimanesh & Jenkins, 2021) Asia (Ismail, 2020) Gulf and Caribbean (von der Ptten, 2021) show that trade facilitation is mainly enhanced by the integration of the revenue administration agencies in the member countries. This having not been empirically proven in the region and particularly in the EAC, this study was set to establish the role that the revenue administration authorities/agencies in the EAC member countries play in enhancing trade facilitation in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the total potential welfare gains in the region are estimated to be between USD 1.56 billion and 2.69 billion, amounting to 0.24% to 0.42% of their GDP. Using a similar methodology, Jenkins and Safaeimanesh have reported that the potential economic gains in the South Africa Customs Union (SACU) amount to USD 2.2-3.7 billion in 2018 prices [23]. In this study, the authors include a well-structured single window system amongst the suggested policy options to be implemented in this customs union.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What is more, even the continent's complex agricultural supply chains are challenged by intricate and burdensome import and export procedures (Kareem et al, [7]). Available statistics reveal the customs clearances are often involved in long delays, even for perishable goods that require minimum clearance times (Kuteyi,& Winkler,[8]; Safaeimanesh, S., & Jenkins, [9]). Instances abound, in Kenya, permits to legally import grains are available only in Nairobi (Nyameino, Kagira and Njukia [10]).…”
Section: Introductionmentioning
confidence: 99%